Can biodiversity of preexisting and created salt marshes match across scales? An assessment from microbes to predators. Issue 3 (15th March 2023) - Keppeler, Friedrich W.; Junker, James R.; Shaw, Margaret J.; Alford, Scott B.; Engel, Annette S.; Hooper‐Bùi, Linda M.; Jensen, Olaf P.; Lamb, Katelyn; López‐Duarte, Paola C.; Martin, Charles W.; McDonald, Ashley M.; Olin, Jill A.; et al.
Abstract: Coastal wetlands are rapidly disappearing worldwide due to a variety of processes, including climate change and flood control. The rate of loss in the Mississippi River Delta is among the highest in the world and billions of dollars have been allocated to build and restore coastal wetlands. A key question guiding assessment is whether created coastal salt marshes have similar biodiversity to preexisting, reference marshes. However, the numerous biodiversity metrics used to make these determinations are typically scale dependent and often conflicting. Here, we applied ecological theory to compare the diversity of different assemblages (surface and below‐surface soil microbes, plants, macroinfauna, spiders, and on‐marsh and off‐marsh nekton) between two created marshes (4–6 years old) and four reference marshes. We also quantified the scale‐dependent effects of species abundance distribution, aggregation, and density on richness differences and explored differences in species composition. Total, between‐sample, and within‐sample diversity (γ, β, and α, respectively) were not consistently lower at created marshes. Richness decomposition varied greatly among assemblages and marshes (e.g., soil microbes showed high equitability and α diversity, but plant diversity was restricted to a few dominant species with high aggregation). However, species abundance distribution, aggregation, and density patterns were not directly associated with differences between created and reference marshes. One exception was considerably lower density for macroinfauna at one of the created marshes, which was drier because of being at a higher elevation and having coarser substrate compared with the other marshes. The community compositions of created marshes were more dissimilar than reference marshes for microbe and macroinfauna assemblages. However, differences were small, particularly for microbes. Together, our results suggest generally similar taxonomic diversity and composition between created and reference marshes. This provides support for the creation of marsh habitat as tools for the maintenance and restoration of coastal biodiversity. However, caution is needed when creating marshes because specific building and restoration plans may lead to different colonization patterns.